Comparison of LTE Network Download Upload FDD and TDD Technology - Yuhanef, Afrizal; Chandra, Dikky; Amanda, Alifia (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2025)
Data communication like download and upload are mostly used in utilizing downlink and uplink channel in data transceiver. This research analyzed comparison of download and upload Time Division Duplex (TDD) 2100 Mhz and Frequency Division Duplex (FDD) 2300 Mhz under bandwith 20 MHz using drive test. Based on The Key Performance Indicator (KPI) of Telkomsel, average Reference Signal Received Power (RSRP) of FDD is better with very good category (-95 until -80 dBm) amounted -91.4 dBm and -89.4 dBm, while TDD namely -98,2 dBm dan -97,6 dBm. Average signal to Interference Noise Ratio (SINR) of TDD was better include into very good category (10 until 20 dB) amounted 13.4 dB and 12.1 dB, while FDD namely 8,9 dB dan 7,4 dB. Average Throughput Download in PDCP (Packet Data Convergence Protocol) and Physical Layer TDD was better with very good category (500 until 100000 kbps) namely 22457.3 kbps and 26842.3 kbps, while FDD namely 18687.7 kbps and 21790.6 kbps. Average Throughput Upload in PDCP and Physical Layer FDD was better, included into very good category (3000 – 5000 kbps) namely 3733.12 kbps and 4425.9 kbps, while TDD reached 2832.34 kbps and 3175.4 kbps. The research result showed that the best parameter in FDD (RSRP and Throughput Upload) and TDD (SINR, CQI, Throughput Download), fulfilled KPI Very Good Category.